Analisis Penerapan Prosedur Audit Persedian dan Tantangan Auditor dalam Menilai Keandalan Data untuk Menimalisi Resiko Salah Persediaan pada Entitas Bisnis - Angraini Angraini; Muh. Awal; Masyuri Masyuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the implementation of inventory audit procedures and the challenges faced by auditors in assessing the reliability of inventory data to minimize the risk of material misstatement in business entities. The research adopts a descriptive qualitative approach using documentation studies of audit reports, audit guidelines, and relevant academic literature. The findings indicate that inventory audit procedures, including physical stocktaking, vouching, evaluation of internal control systems, and the use of audit technology, play a crucial role in enhancing the reliability and accuracy of inventory data. However, auditors encounter various challenges, such as poor initial data quality, complex inventory systems, limited auditor competence, time constraints, and the impact of digital transformation. These challenges require auditors to apply risk-based audit planning, strengthen professional judgment, and continuously improve their technical and analytical skills. The study concludes that effective and consistent inventory audit procedures, supported by strong internal controls and adaptive audit strategies, are essential to reduce inventory misstatement risks and ensure the credibility of financial statements. This research contributes to the development of audit practices by emphasizing the importance of auditor adaptability in a dynamic business environment.